PATHOGENIC REACTIVITY OF ANATOMICAL AND FUNCTIONAL SYSTEMS OF THE BODY - Леонид Николаевич Иванов; Марина Леонидовна Колотилова; Наталья Викторовна Алексеева (Медицина в Кузбассе, 2023)
Development of concepts of teaching pathogenic individual reactivity of the organism at the level of anatomical and functional systems.